Bioinformatics Analysis of Comorbidity Genes in Chronic Kidney Disease and Heart Failure and the Application of Traditional Chinese Medicine - Liu, Chang; Li, Xiaohui (Journal of Contemporary Medical Practice, 2025)
Objective: To identify and validate the overlapping genes between Chronic Kidney Disease (CKD) and Heart Failure (HF) using bioinformatics techniques, predict Chinese herbs targeting these genes, and explore the findings in the context of the traditional Chinese medicine theory of “Yang Wei Yin Xian”. Methods: The datasets of CKD and HF were obtained from the GEO database. Differential analysis was performed in R 4.4.1, and Venn diagrams were used to select overlapping differentially expressed genes. Enrichment analysis was conducted to investigate the main pathways and biological significance. Three machine learning methods were applied to further screen the genes, and the pROC package was used to plot the receiver operating characteristic curves and calculate the area under the curve. The correlation between characteristic genes and immune cells was studied through immune infiltration analysis. The GeneMANIA database was used to find homologous genes, and the COREMINE Medical database was used to predict Chinese herbs targeting the key genes. Results: A total of 75 overlapping genes between CKD and HF were identified. Gene Ontology (GO) analysis showed enrichment mainly in positive regulation of transferase activity, positive regulation of inflammatory response, etc. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis showed enrichment mainly in the HIF-1 signaling pathway, ferroptosis, etc. Three machine learning methods were used to screen the overlapping genes, and 11 core target genes were obtained by taking the intersection. Five genes (CYBB, MME, IFIT3, FCGR1B, C4orf29) with an AUC>0.7 were identified using the “pROC” package. These five genes were uploaded to the GeneMANIA database, and 25 homologous and functionally related target genes were obtained. Finally, 84 Chinese herbs, including Scutellaria baicalensis, soft-shelled turtle carapace, Polyporus umbellatus, and Gnaphalium affine, were predicted using the COREMINE Medical database. These herbs are mainly heat - clearing and detoxifying herbs, tonics, blood - activating and stasis - resolving herbs, and diuretic and dampness - draining herbs. The conclusions were also explored in the context of the traditional Chinese medicine theory of “Yang Wei Yin Xian”. Conclusion: This study found that the five genes FCGR1B, CYBB, C4orf29, MME, and IFIT3 are of great significance in the research and treatment of CKD combined with HF in both traditional Chinese and Western medicine. Chinese herbs with the effects of clearing heat and detoxifying, nourishing Yin and enriching marrow, and inducing diuresis to reduce edema can be helpful in treatment. The screening results were also found to be closely related to the traditional Chinese medicine theory of “Yang Wei Yin Xian”.